A lithium-ion battery electrochemical–thermal model for a wide temperature range applications. (1st December 2020) - Wang, Dafang; Huang, Huanqi; Tang, Zhihao; Zhang, Qi; Yang, Bowen; Zhang, Bi
Highlights: Established a discrete electrochemical–thermal model of lithium-ion battery. Updated model parameters according to battery internal temperature. Validated the model under different current and temperature conditions. Simulated the 'trough' phenomenon at −20 °C successfully. Abstract: The internal temperature of lithium-ion battery affects the battery parameters during discharge and charge process, and the low-temperature environment has a particularly significant impact on the performance of the lithium-ion battery. In this paper, a simplified discrete electrochemical model adapts to a wide temperature range is developed. Based on Pseudo-Two-Dimension (P2D) model, we simplify the governing equation to describe the solid and solution diffusion by fitting the lithium-ion concentration in the form of parabolas. Analysis of the heat generation and dissipation conditions of lithium-ion batteries is conducted, and a concentrated mass thermal model is established to describe the internal temperature changes of batteries. The parameters involved in the electrochemical model are also updated accordingly. Finally, an electrochemical–thermal coupling model is established. In order to verify the cell potential difference simulation accuracy of the model, the constant current discharge conditions, DST (Dynamic Stress Test) in the ambience above 0 °C and the multi-stage current discharge conditions in the ambience below 0 °C is carried out. The results show that the model with parameters update significantly improves the accuracy of simulation, especially at low temperature (−20 °C, −10 °C, 0 °C). What's more, the model with parameter update can simulate the potential difference's 'trough' phenomenon in the constant current phase of the pulse discharge at -20°C better than the model without parameter update.